(untitled) (Studi di storia medioevale e di diplomatica - Nuova Serie, 2021)
The article analyses the presence of pre‐12th‐century documents in the libri iurium of the cities of medieval lombardy. There are a good number of documents, but most of them are munimina, which only later entered the archives of the municipality and then transcribed in the libri iurium. We can think that the communes did not claim any continuity, at least from a documentary point of view, with the royal and episcopal institutions that preceded them. It is a different matter, however, for the initiatives taken autonomously by the city communities, which, at least in the case of Cremona and Mantua, already by the end of the tenth cen‐ tury seem to have been able to request and preserve important imperial doc‐ uments, transmitting them to the later municipal institutions.